Konsensdemokratie und Nationenbildung im Irak und in der Autonomen Region Kurdistan - Karim, Abaas (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
Abaas Karim, who migrated from Iraq to Switzerland as a refugee more than twenty years ago, starts this dissertation from the basic assumption that both for Iraq as a whole and for the Autonomous Region of Kurdistan (ARK) in the north of Iraq, the path towards nation-building is far from complete and that, in view of the ethnic/confessional and political fragmentation of both Iraq and the ARK in particular, the political order of a federalist consensual democracy based on the Swiss model should be striven for. He comes to this conclusion after drawing on Kurdish–Iraqi research literature in particular on the period before 2003. For the years 2003–2018, A. Karim systematically evaluates the two daily newspapers Xebat, the mouthpiece of the DPK (Democratic Party of Kurdistan), and Kurdistan Nwe, the newspaper of the PUK (Patriotic Union of Kurdistan) since 1992, as well as the independent media network Hawlati (‘Citizens’). Abaas Karim has been working for the Swiss Armed Forces since 2014 and is responsible for its Middle East dossier.